Cdc28 Activates Exit from Mitosis in Budding Yeast - Rudner, Adam D.; Hardwick, Kevin G.; Murray, Andrew W. (The Journal of cell biology, 2000)
The activity of the cyclin-dependent kinase 1 (Cdk1), Cdc28, inhibits the transition from anaphase to G1 in budding yeast. CDC28-T18V, Y19F (CDC28-VF), a mutant that lacks inhibitory phosphorylation sites, delays the exit from mitosis and is hypersensitive to perturbations that arrest cells in mitosis. Surprisingly, this behavior is not due to a lack of inhibitory phosphorylation or increased kinase activity, but reflects reduced activity of the anaphase-promoting complex (APC), a defect shared with other mutants that lower Cdc28/Clb activity in mitosis. CDC28-VF has reduced Cdc20-dependent APC activity in mitosis, but normal Hct1-dependent APC activity in the G1 phase of the cell cycle. The defect in Cdc20-dependent APC activity in CDC28-VF correlates with reduced association of Cdc20 with the APC. The defects of CDC28-VF suggest that Cdc28 activity is required to induce the metaphase to anaphase transition and initiate the transition from anaphase to G1 in budding yeast.